Intercultural Coping for the Jurisdictional Coordination: the Colombian Case in the Latin-American Perspective - Zambrano, Carlos Vladimir (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2008)
This article has been organized on a field-work carried out in Colombia, with intercultural focal groups, during two years. Fifty authorities from fifty indigenous peoples and fifty judges and magistrates of the national judicial system who have intervened in judicial processes against indigenous authorities, participated in such groups. It is the purpose to present the jurisdictional coordination within an intercultural, ethnographic and processual perspective, in as much as that institution is central in the Social Work treatment of the intercultural, whenever two juridical systems are judicially related. The focal groups permitted to catch with method a glimpse of the difficulties and possibilities of the interculturallity between indigenous authorities and judges of the judicial branch, besides fixing anthropological, political and juridical positions of intercultural bearing. That we are prompt to present within the Latin-American vision.